2019
DOI: 10.1097/crd.0000000000000283
|View full text |Cite
|
Sign up to set email alerts
|

Very Late Stent Thrombosis in Drug-Eluting Stents New Observations and Clinical Implications

Abstract: Despite the reduction in stent failure with newer-generation drug-eluting stents, very late stent thrombosis (VLST) remains an unpredictable and potentially catastrophic complication of coronary revascularization procedures and is associated with high morbidity and mortality. Here, we present an updated overview of the latest advances in understanding the causes of VLST. Clinical studies that revealed potential risk factors and pathophysiologic studies on the mechanisms of VLST are discussed. Importantly, nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…[5] Previous reports have shown that the risk of VLST persists even until five years post DES implantation. [4] Predictors for late ST/VLST include younger patients, smokers, STEMI at time of initial DES implantation, number of diseased vessels, type C lesions, longer stent length and presence of overlapping stents. [6] The risk of VLST at the time of DES implantation can be estimated by a recently proposed "VLST scoring system".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Previous reports have shown that the risk of VLST persists even until five years post DES implantation. [4] Predictors for late ST/VLST include younger patients, smokers, STEMI at time of initial DES implantation, number of diseased vessels, type C lesions, longer stent length and presence of overlapping stents. [6] The risk of VLST at the time of DES implantation can be estimated by a recently proposed "VLST scoring system".…”
Section: Discussionmentioning
confidence: 99%
“…It does, however, have life-threatening consequences resulting in acute MI or death, with mortality reported to be as high as 45%. [4] We present a middle-aged male with a prior history of coronary artery disease (CAD), who developed acute ST-segment elevation myocardial infarction (STEMI) due to VLST occurring two years after DES implantation following COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Stenting with a DES reduces target vessel revascularization (TVR) but there is no benefit in aborting recurrent AMI [4]. This was shown in a study that demonstrated an increased incidence of stent thrombosis among AMI patients treated with DES as compared with balloon angioplasty alone, thus paving a potential role of a DCB in PPCI [5]. The presence of a drug on the semi-compliant DCB provides a potential advantage in reducing the potential risk of in-stent restenosis or stent thrombosis [12].…”
Section: Discussionmentioning
confidence: 99%
“…Drug-eluting stents (DES) are implanted in the blocked arteries after the restoration of thrombolysis in myocardial infarction (TIMI) flow during PPCI [3]. Various large trials have proven DES to reduce repeat revascularization, however, they do not reduce mortality as compared to balloon angioplasty alone and it increases the long-term risk of stent thrombosis and stent restenosis [4][5].…”
Section: Introductionmentioning
confidence: 99%
“… 1 Very late stent thrombosis (VLST, stent thrombosis occurring more than 1 year after stent implantation, usually out of the time window recommended by the guidelines for antiplatelet therapy and often overlooked) is an uncommon yet catastrophic event after PCI, usually manifesting as recurrent AMI with poor prognosis or sudden death. 2 , 3 Despite being recognized for over a decade, the detailed mechanisms underlying VLST remain poorly understood, and the insights that can translate into prediction, precaution, and management of VLST are lacking.…”
Section: Introductionmentioning
confidence: 99%